New Optimization Strategy of Thermoelectric Coolers Applied to Automotive and Avionic Applications. (2015) - Caroff, Tristan; Sarno, Claude; Hodot, Romain; Brignone, Mauro; Simon, Julia
Abstract: This paper deals with a new generic approach for multi-criteria optimization of thermoelectric coolers using multi-physic simulations. This approach is based on the determination of the optimal thermal resistance of a thermoelectric cooler in defined thermal environment. This new methodology is used to define optimized Peltier coolers for two specific applications studied in the frame of NANOTEG Eniac project: cooling of FPGA based processor for the next generation helicopters for Thales Aerospace Division and low power consumption solid state air-conditioning system for Fiat Research Center. This paper is a part of a series of planned publications on the ongoing work in the NANOTEG project.